Zmiany struktur własnościowo-kontrolnych w warunkach kryzysu gospodarczego - Urbanek, Piotr (Changes in Ownership and Control Structures During the Period of Economic Crisis, 2009)
There are two types of corporations ownership and control structures which are termed "insider" and "outsider" systems. In "outsider" system, typical for American and British companies, ownership is dispersed among a large number of small investors. In "insider" system there is one large investor holding a dominant block of shares. Polish public companies operate within insider system of corporate control. Median voting block for first largest shareholder amounts to over 40%. The purpose of the paper is to identify changes in patterns of ownership and control in Polish public companies. The analysis was conducted for two periods: 2006 and the beginning of 2009. The first period was a bull market, during the second period we can observe unprecedented decline in world capital market (also Warsaw Stock Exchange). The hypothesis verified in the paper can be formulated as following: how processes of merges and acquisitions observed on Warsaw Stock Exchange, determined by financial and economic crisis stimulate efficiency of external mechanisms of corporate control, and to what extend such external control mechanisms can support internal mechanisms in the process of creation shareholders wealth. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 867-878